Evaluation of Nursing Students' Level of Knowledge of Blood Pressure and Indirect Blood Pressure Measurement Skills Using a Simulator - Emine Derya İster; Merve Gülpak; Ayşe Asli Oktay Gök (Artuklu Health, 2026)
Introduction: The aim of this study was to evaluate nursing students’ knowledge of blood pressure and their skills in indirect arterial blood pressure measurement using an arm simulator designed for arterial blood pressure training. Methods: The sample of the cross-sectional descriptive study consisted of 173 nursing students. Researchers collected data using a student information form, blood pressure measurement chart, and blood pressure knowledge test. The accuracy of the students’ blood pressure measurements was evaluated with the ‘Arterial Blood Pressure Training Application Arm Simulator.’ Statistical significance was set at p0.05). Conclusion: This study highlights that alongside theoretical education, the use of simulation models is crucial for teaching nursing students blood pressure measurement skills effectively.